Environmental Kuznets Curve Approach to Estimate Ecological Footprint in Pakistan - Yamin, Rukhsar; Hanif, Uzma; Anwar, Muhammad Awais; Arshed, Noman (Pakistan Journal of Humanities and Social Sciences, 2023)
The aim of the study is to explore the various variables that lead to Pakistan's environmental deterioration. The impact of macroeconomic factors of environmental deterioration is investigated to fulfill the objective of the study. The impact of determinants on environmental degradation from 1990 to 2020 was explored in this study. The dependent variable is Ecological Footprint, which is used as a proxy for environmental deterioration, whereas the independent variables are Trade openness, Urbanization, foreign direct investment, and per capita income growth. However, square of per capita also included in a model to verify the phenomena of Kuznets curve. The variable's stationarity was checked and used the unit root test (ADF and PP), which indicated that it exists at the first difference. According to the result of stationary ARDL cointegration model is applied. The result of the test showed the long run relation among the variable. The coefficient of GDP is positive and squared GDP is negative, this means that if there is a consistent rise in GDP, then the negative effect of squared GDP will overcome the positive effect of level GDP. Beyond this point increase in GDP will reduce the ecological footprint. This phenomenon was discussed earlier as the environmental Kuznets curve.